Microstructure and Characterization of Detonation Gun Sprayed Al2O3 Coating - Singh, Lakhwinder; Grover, Neel Kanth; Chawla, Vikas; Grewal, J. S. (Asian Journal of Engineering and Applied Technology, 2016)
Thermal spraying is economic and extensively used method to develop coatings on various materials to achieve desired surface properties. Coatings are widely used in different applications of material, like in automotive system, power generation equipments, orthopedics and dental use etc. Detonation gun spraying is one of the thermal spraying technique known to produce dense microstructured, hard and wear resistant coating. In this work Al2O3 Coating was deposited on substrate of Grade-A1 boiler tube steel by detonation gun spraying technique. The characterization of coating was done by Scanning Electron Microscopy (SEM), XRay diffraction (XRD), and X-Ray Mapping.